Differentials and correlates of infants mortality in Nigeria: A comparative survival Analysis between North East and South West Nigeria (2014)
Aims: Infant mortality rate (IMR) is not only used as a demographic measure, but also as an important health indicator of a society as well as a measure of its living standard worldwide. The Nigeria Demographic and Household Survey (NDHS) declared a wide difference in the IMR among geographical zones in Nigeria with widest gap between the North East (NE) and South West (SW). This study assessed the differences in IMR viz-a- viz socio-demographic, sexual and reproductive factors and also determined factors affecting the IMR in the two zones. Place of Study: Rural and Urbanlocations across the NE and SW Nigeria Study Design: We used a nationally representative cross sectional data from the NDHS 2008 survey.Our analysis was based on the 23,995 and 11,546 births during five years preceding data collection from women aged 15-49 years in NE and SW Nigeria respectively. Methods: We censored the children who have not had their first birthday as of the day of interview and estimated the IMR with Life tables using West Models. Other analysis were carried out with descriptive statistics, bivariate and multivariate cox regression models at 5% significance level. Results: About 3 of every four NE children are from rural areas compared with 47.4% in SW, while nearly 78% of NE children are from mothers without formal education the rate was 20.9% in the SW. The IMR among children from teenager mothers was 121 and 82 per 1000 live births in NE and SW respectively, 87 for urban NE, 52 for urban SW, 115 for rural NE, and 66 for rural SW. In the NE, children from rural areas were about 30% times more likely than children from urban areas to die before their first birthday (HR=1.3 95% CI:1.1-1.6)while in the SW they were 40% times more likely to die (HR=1.6 95% CI:1.1- 2.4). Children from wealthiest homes in the NE had lower IMR than children from wealthiest homes in the SW (37 vs 55) but wealth quintiles were not significant to IMR in the SW. Conclusion: The prevailing trend of early marriage, non-education, delayed initiation of breastfeeding, unsafe drinking water, unemployment and poverty among others should be averted so as to improve child survival in the Nigeria especially in the North East.